Comparative Study of Hierarchical Routing Protocols in Wireless Sensor Networks - Singhal, Vishakha; Suri, Shrutika (International Journal of Computer Sciences and Engineering, 2014)
Wireless sensor networks (WSN) comprise a wide variety of applications in every field. Wireless sensor networks consist of small nodes with numerous capabilities such as sensing, computation, and wireless communications. Main area of concern in wireless sensor network is energy. As sensor in wireless sensor networks works on battery and have limited energy, therefore they have a limited lifetime. There comes the idea of hierarchical clustering. Hierarchical clustering of nodes and routing as per clusters contributes in reducing energy consumption and increasing lifetime of a network. This paper presents the study of hierarchical-based routing protocols (HBRP) such as leach and pegasis protocol proposed for wireless sensor networks. Additionally, the paper includes the comparison analysis of both protocols based on some parameter.